Multiple hepatic and brain abscesses caused by Parvimonas micra: A case report and literature review. (June 2021) - Cesta, N.; Foroghi Biland, L.; Neri, B.; Mossa, M.; Campogiani, L.; Caldara, F.; Zordan, M.; Petruzziello, C.; Monteleone, G.; Fontana, C.; Andreoni, M.; Sarmati, L.
Abstract: Gram-positive anaerobic cocci (GPAC) are responsible for 30% of anaerobic infections. Parvimonas micra is an emergent pathogen that is part of the oral and gastrointestinal commensal flora, and its role in several infection processes has recently emerged thanks to the improvement of diagnostic techniques. P. micra bacteraemia is reported in immunocompromised patients and is often complicated by abscesses. Here, we present a case study of multiple hepatic and brain abscesses caused by P. micra bacteraemia in a patient with complicated diverticulitis. Highlights: Parvimonas micra ( P.micra ), a Gram-positive anaerobic coccus, is commonly part of the oral and gastro-intestinal flora. Thanks to advanced bacterial identification techniques, P. micra is emerging as cause of epidural, brain and intra-abdominal abscess. In case of P. micra bacteraemia and abscesses, diverticulitis should be considered as a possible source of infections.